Phytochemical Profiling and in vitro Screening for Neuritogenic and Antioxidant Activities of Spirulina platensis - Ngu, Ee-Ling; Ko, Chen-Lin; Tan, Cheng-Yau; Wong, Kah-Hui; Phang, Siew-Moi; Yow, Yoon-Yen (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: In neurological diseases, neuronal loss is frequently associated with overproduction of free radicals and reduced level of endogenous neurotrophic factors. The blue-green microalga, Spirulina platensis is a well-known superfood with a high content of diverse nutrients and possesses several therapeutic properties. Here, we aimed to study the neuritogenic and antioxidant activities of Spirulina platensis UMACC 159. Materials and Methods: PC-12Adh (rat pheochromocytoma) cell was used to investigate the cytotoxicity effect of S. platensis UMACC 159 extracts (water, methanol, and ethanol) via 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Neuritogenic activity of the extracts towards PC-12Adh cell line was studied using neurite outgrowth assay and immunofluorescence imaging of neurofilaments. The extracts were screened for the phytochemical contents, and antioxidant activities using 2,2’-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-Diphenyl-1-pircrylhydrazyl (DPPH) and reducing power. Results: Ethanol extract was found to exhibit the highest neuritogenic effect and enhanced the cytoskeleton formation in PC-12Adh cells at 6.25 µg/mL. Ethanol extract also showed the highest total phenolic content (49.09 ± 1.35 mg GAE/g), ABTS (EC50 of 1.34 ± 0.01 mg/mL) and DPPH (EC50 of 0.45 ± 0.04 mg/mL) scavenging activities (P ≤ 0.05), suggesting that the neuritogenic effect of ethanol extract was attributed to the phenolic compound(s) via antioxidant activity. Conclusion: Ethanol extract contains bioactive compound(s) with similar neuritogenic activity as nerve growth factor for neuronal survival, growth, and axonal regeneration. S. platensis has been proposed as a promising cognitive supplement.
Keywords: Spirulina platensis; Antioxidants; Cytotoxicity; Neuronal outgrowth; Phytochemicals